Christians in the Holy Land - Prior, Michael; Sabella, Bernard; Abu-el-Assal, Riah; Sarraf, Faraj al-; Geraisy, Sami F. (The World of Islam Festival Trust, 1994)
Anthony O'Mahony: Church, state and the Christian communities and the holy places of Palestine. - S. 11-27. - zahlr. Lit.Hinw. Bernard Sabella: Socio-economic characteristics and the challenges to Palestinian Christians in the Holy Land. - S. 31-44. - zahlr. Lit.Hinw. Sami F. Geraisy: Socio-demographic characteristics: reality, problems and aspirations within Israel. - S. 45-55. - zahlr. Lit.Hinw. Faraj al-Sarraf: Christianity in Gaza. - S. 57-63. Jean Zaru: Justice and peace. - S. 65-73. Jacqueline Sfeir: Education in the Holy Land. - S. 75-88. - Tab. Jeanne Kattan: A study of Muslim and Christian students' attitudes towards each other at Bethlehem University. - S. 89-97. Albert Aghazarian: The significance of Jerusalem to Christians. - S. 99-106. Maroun Lahham: The spiritual meaning and experience of the Roman Catholic Church in Jerusalem. - S. 109-114. Harry Hagopian: The Armenians of Jerusalem in the Armenian Quarter. - S. 115-125. Mitri Raheb: The spiritual significance and experience of the Churches: the Lutheran perspective. - S. 127-130. Riah Abu El-Assal: The birth and experience of the Christian Church: the Protestant/Anglican perspective. Anglican identity in the Middle East. - S. 131-140. Gabriel Baramki: The spiritual significance and experience of the Churches: the Orthodox perspective. - S. 141-142. Salim J. Munayer: Relations between religions in historic Palestine and the future prospects: Christians and Jews. - S. 143-150. Kenneth Cragg: Beginning at Jerusalem. The Church's story, then and now. - S. 153-159. Michael Nazir Ali: Christians in the Holy Land. - S. 161-168. Michael Prior: Pilgrimage to the Holy Land, yesterday and today. S. 169-199. - zahlr. Lit.Hinw., Lit. S. 198-199. Agnes D. Hanania: Churches of the Holy Land: obligations and expectations. A view from the Holy Land. - S. 203-216. - Lit. S. 215-216. Hugh Wybrew: Churches of the Holy Land: obligations and expectations. A view from outside. - S. 217-223